1994
DOI: 10.1177/036354659402200208
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Intercondylar Notch Stenosis and Correlation to Anterior Cruciate Ligament Injuries

Abstract: To evaluate the possible relationship between femoral intercondylar notch stenosis and anterior cruciate ligament injuries in pivoting and cutting sports, a 2-year prospective study was performed on intercollegiate athletes at a Division I university. Daily practice times and athlete participation in practices and games were recorded for each sport during the 2-year period. Bilateral intercondylar notch view radiographs were taken of all athletes enrolled in the study. The notch width index, a ratio that measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
199
0
18

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 298 publications
(227 citation statements)
references
References 33 publications
10
199
0
18
Order By: Relevance
“…Our finding that a lower NWI index may predispose to ACL injury in the paediatric population is in accordance with previous studies looking at young adult populations [2][3][4][5][6][7]20]. While there is still disagreement in the literature as to whether variations in notch geometry related to differences in gender or limb dominance, play a contributing role in ACL injuries, we did not find a difference in NWI with respect to gender, involved side, mechanism of injury or type of sport engaged in at the time of injury [7,12,13,18,21,22].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our finding that a lower NWI index may predispose to ACL injury in the paediatric population is in accordance with previous studies looking at young adult populations [2][3][4][5][6][7]20]. While there is still disagreement in the literature as to whether variations in notch geometry related to differences in gender or limb dominance, play a contributing role in ACL injuries, we did not find a difference in NWI with respect to gender, involved side, mechanism of injury or type of sport engaged in at the time of injury [7,12,13,18,21,22].…”
Section: Discussionsupporting
confidence: 93%
“…This difference may be caused by different imaging techniques used for the evaluation of NWI. Two studies measuring NWI using MRI [8,21] have shown much higher values for normal adult populations than values reported in radiographic studies [2][3][4][5][6][7]20].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations